Oral Administration of N-acetylcysteine Improves Biochemical Parameters in Diabetic Rats - Gonçalves, Jamile Fabbrin; Mazzanti, Cinthia Melazzo; Becker, Alexssandro Geferson; Kaizer, Rosilene Rodriguez; Battisti, Vanessa; Corrêa, Maísa de Carvalho; Maldonado, Paula Acosta; Schmatz, Roberta; Thomé, Gustavo Roberto; Morsch, Vera Maria; Schetinger, Maria Rosa Chitolina (Ciência e Natura, 2012)
To evaluate the effect of N-acetylcysteine (NAC), a potent ROS scavenger and thiol group supplier, on normoglycemic and diabetic rats, the animals received 50 or 200 mg/kg NAC by gavage daily for 45 days. The results showed a lack of uniformity in acetylcholinesterase activity among the four cerebral structures. While neither dose of NAC produced significant hypoglycemic activity, 50 mg/kg NAC partially reverted the weight loss of diabetics and was effective in restoring aminolevulinate dehydratase activity and non-protein thiol content in liver, and in diminishing serum protein carbonylation. The dose of 200 mg/kg NAC presented some negative effects per se in both the antioxidant and cholinergic systems. In conclusion, 50 mg/kg NAC produced an improvement in some parameters suggesting NAC as a possible drug in antioxidant therapies against diabetic state. However, future studies are necessary to investigate the better dose of this compound to counteract its undesirable effects.